2000
DOI: 10.1111/j.1741-3737.2000.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Parent‐Adolescent Language Use and Relationships Among Immigrant Families With East Asian, Filipino, and Latin American Backgrounds

Abstract: ࡗ Parent-Adolescent Language Use and Relationships Among Immigrant Families With East Asian, Filipino, and Latin American BackgroundsThis study examined differences in the quality of relationships between immigrant parents and their adolescent children as a function of the languages with which they speak to one another. Over 620 adolescents with East Asian, Filipino, and Latin American backgrounds completed measures on parent-adolescent language use and relationships. Adolescents who spoke in different languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
215
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(231 citation statements)
references
References 20 publications
11
215
5
Order By: Relevance
“…Similar hypotheses about a potentially corrosive effect of U.S. culture on health and well-being have been suggested for Latino immigrant groups [24,25]. One study found that U.S. parents and adolescents from East Asian, Filipino, and Latino backgrounds who continued to communicate in their native language reported better relationship quality than those who communicated in English [26].…”
mentioning
confidence: 78%
“…Similar hypotheses about a potentially corrosive effect of U.S. culture on health and well-being have been suggested for Latino immigrant groups [24,25]. One study found that U.S. parents and adolescents from East Asian, Filipino, and Latino backgrounds who continued to communicate in their native language reported better relationship quality than those who communicated in English [26].…”
mentioning
confidence: 78%
“…According to Tseng and Fuligni (2000), parents and children who are less discrepant in their acculturation levels are able to use the same language in communicating with each other, increasing the likelihood of parent-child communication and parents' transmission of values onto their children. This shared understanding and communication can foster a positive parent-child relationship within the family (Kim 1995).…”
Section: Cultural Adaptation At the Family Levelmentioning
confidence: 98%
“…There are other aspects of parent-child relationships, however, that may play an important role in understanding the ways in which acculturation gaps function within families. For example, during adolescence, preserving a sense of connection with parents is critical [Steinberg & Silk, 2002], yet acculturation gaps in language preferences and proficiencies can present concrete obstacles to effective communication and problem solving, making it more difficult to discuss sensitive emotional issues and limiting parents' support for their children as they confront the challenges of adolescence and of navigating a multicultural environment [Costigan & Dokis, 2006b;Tseng & Fuligni, 2000;Yee, Huang, & Lew, 1998]. This reduction in feelings of connection, belonging, or sense of being understood may negatively impact youth adjustment independent of levels of parent-child conflict.…”
Section: What Are the Mechanisms That Transmit Potential Risk?mentioning
confidence: 99%